Fabrication and electro-optic properties of 0.9Pb[(Mg, Zn)1/3Nb2/3]O3–0.1PbTiO3 transparent ceramics by a conventional sintering technique. (20th September 2017) - Fujii, Ichiro; Nakashima, Saki; Wada, Takahiro
Abstract: 0.9Pb[(Mg1− x Zn x )1/3 Nb2/3 ]O3 –0.1PbTiO3 ( x = 0–0.4) ceramics were fabricated by a conventional sintering technique. The ceramics became transparent at x = 0, 0.1, and 0.2, and the transmittances were 47, 43, and 53% at an infrared wavelength of 1310 nm, respectively. Birefringence of the transparent ceramics was quadratically increased as a function of electric field, with some deviations observed beyond certain electric fields at x = 0 and 0.2. An effective quadratic electro-optic (EO) coefficient was calculated with a half-wave electric field, and it was 6.30, 25.5, and 13.8 × 10 −16 m 2 /V 2 at x = 0, 0.1, and 0.2, respectively. The large EO effect at x = 0.1 was associated with the composition where a transition from a relaxor state to a ferroelectric state occurred. Microstructure, density, refractive index, and dielectric and ferroelectric properties were also investigated.